ANALISIS PERHATIAN DAN KETERLIBATAN SISWA PADA PEMBELAJARAN SECARA DARING - Nasution, Futri Ramadhani; Adlika, Nur Meily; Tampubolon, Budiman (Universitas Tanjungpura, 2022)
The background in this study discusses student interest in learning geography during the covid-19 pandemic. This study aims to determine how happy feelings, student interest, student attention, and student involvement in learning geography online. The research method used is qualitative research. This research was conducted at SMA Negeri 2 Sungai Raya by interviewing seven students in class XI Social Sciences based on the recommendations given by the teacher and geography teacher for class XI Social Sciences at SMA Negeri 2 Sungai Raya. The study results indicate that students are diligent in attending and have feelings of pleasure in participating in online geography learning activities. Students are less interested in studying geography outside class hours because they only learn when there are assignments or tests. Students sometimes have problems understanding the material given by the teacher, but students want to try to understand the material provided by the teacher. The involvement of students in learning, including less due to the absence of discussion between teachers and students. This study concludes that students still are interested in learning geography online, but the overall indicators are not good. Because there is a lack of student involvement in online geography learning, most students feel obstacles in understanding the material given by the teacher.